PENICILLINASE PLASMID DNA FROM Staphylococcus aureus - Rush, Mark G. (1969)
A penicillinase plasmid from Staphylococcus aureus and three of its derivatives, all previously identified as extrachromosomal genetic elements, have been isolated in high yield as circular duplex DNA molecules. The wild-type plasmid was found by contour-length measurements of electron micrographs to have a molecular weight of 18.6 × 10(6) daltons. Two plasmids with deletions encompassing six and eight of the eleven known plasmid cistrons had molecular weights of 16.4 × 10(6) and 15.3 × 10(6) daltons, respectively. This information was used to establish approximate physical distances for the genetic map. A high-frequency transducing element also derived from the plasmid had a molecular weight of approximately 24 × 10(6) daltons. Although each plasmid preparation appeared homogeneous by ultracentrifugal analysis, electron micrographs always revealed the presence of a low percentage of complex oligomeric forms, particularly circular and catenated dimers.